WELL-BEING AT WORK: PERCEPTION OF HUMAN RESOURCES MANAGERS- AN EXPLORATORY CONTEXTUALIZATION STUDY - Siham Chandad,; Rochdane Hanane, (PEOPLE: International Journal of Social Sciences, 2025)
In a context where labor market competitiveness is intense and the quest for productivity is relentless, well-being at work emerges as a crucial pillar and strategic challenge for Human Resources Managers concerning employee performance and retention. HR professionals are increasingly viewed as strategic partners in driving organizational success. This study contributes to the field by deepening the research on HRMs' perceptions of workplace well-being from an employer's perspective. By focusing specifically on how HR professionals perceive and address well-being at work, this research offers valuable insights into their strategic role and the challenges they face. This perspective is crucial for understanding the employer's viewpoint on well-being and for developing targeted strategies that align with organizational goals in Morocco. This study explores the concept of well-being at work from the perspective of HRMs in Morocco through a qualitative study based on semi-structured interviews with HR professionals across various sectors. The theoretical foundation is rooted in Karasek and Theorell's Demand-Control-Support model, Ryff's Psychological Well-Being model, and Seligman's PERMA model. We have chosen an integrative research model that combines these theoretical perspectives to offer a more comprehensive understanding of complex phenomena. The study contributes theoretically by applying these models to the Moroccan context, revealing unique challenges and perceptions that enrich the global discourse on workplace well-being. The study emphasizes that focusing on well-being is crucial for enhancing organizational performance, strengthening employer branding, and reducing turnover. Adopting a strategic approach to well-being can significantly improve organizational outcomes and foster a more engaged workforce. By integrating theoretical models with empirical data, this study provides a robust framework for understanding and enhancing well-being at work, thereby contributing to both academic literature and practical management strategies within the Moroccan context.